The ageless approach: Nonoperative mastery competes head-on with surgery for elderly distal radius fractures - Yalin, Mustafa; Golgelioglu, Fatih; Key, Sefa (Wiley, 2024)
The aim of the current study is to compare the clinical outcomes of cast immobilization (CI) versus surgical treatment after 1 year for distal radius fractures (DRFs) in the elderly population. The cohort included patients aged 70-89 who suffered an acute, closed, and displaced DRF and who were treated conservatively or surgically at our clinic between August 2018 and January 2022. Those who had pathological fractures, open fractures, concomitant ulna fractures (except ulna styloid fractures), were not between the ages of 70 and 89, or refused to participate were excluded from the study. The study gathered data on patient demographics, initial radiological measurements, clinical measurements after 1 year, treatment models employed, and rates of complications. Of the total number of patients (276), CI was used on 77.2% (213), whereas the other 25 had volar-locked plates (VLP), 25 received external fixators with percutaneous pinning (EFPP), and 13 had isolated percutaneous pinning (IPP). 19 of 276 individuals had complications, with Complex Regional Pain Syndrome and Carpal Tunnel Syndrome being the most often documented. EFPP resulted in significantly higher Disability of the Arm, Shoulder, and Hand (DASH) score values than VLP and IPP at the 1st postoperative year (p < 0.05). No statistically significant difference was found between the DASH score and ROM values at the 1st postoperative year for patients who received CI versus those who underwent surgery (p > 0.05). In the first postoperative year, CI still retains its validity and performs similarly to surgery for DRFs in older individuals. VLPP and IPP methods outperformed EFPP surgeries.
Keywords: casting; DASH; distal radius fractures; elderly